1998
DOI: 10.2486/indhealth.36.8
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese Adaptation of the STAI Form Y in Japanese Working Adults. The Presence or Absence of Anxiety.

Abstract: Symptom endorsements and response patterns of 1,862 Japanese adult workers (1,509 males and 353 females) to the Japanese adaptation of the State-TraitAnxiety Inventory Form Y (STAI-JY) items, were examined in this study. The mean STAI-JY State and Trait anxiety scores of Japanese workers were substantially higher than those of American workers reported in the Manual, due primarily to the much higher scores of Japanese workers in responding to the anxiety-absent items. The correlations between the State and Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 10 publications
1
45
2
Order By: Relevance
“…Iwata and his colleagues (44)(45)(46)(47) indicated that self-reported psychological distress is affected among Japanese workers by traditional Japanese culture in relation to age in that older workers are more likely to suppress their expressions of positive feelings than younger workers. For instance, in the Honolulu heart program study, the participants from the Japanese ancestry cohort in Hawaii showed that high job strain appeared to be inversely associated with arteriosclerosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Iwata and his colleagues (44)(45)(46)(47) indicated that self-reported psychological distress is affected among Japanese workers by traditional Japanese culture in relation to age in that older workers are more likely to suppress their expressions of positive feelings than younger workers. For instance, in the Honolulu heart program study, the participants from the Japanese ancestry cohort in Hawaii showed that high job strain appeared to be inversely associated with arteriosclerosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…infusion of ghrelin (3 mg/kg) for 30 min twice a day (before breakfast and dinner) for 14 days (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. After treatment, subjects were hospitalized for an additional 1 week (days [15][16][17][18][19][20][21] to monitor the safety and clinical efficacy of ghrelin treatment. To establish strict quality control, patient enrolment, monitoring, data management, and statistics were conducted independently and separately.…”
Section: Methodsmentioning
confidence: 99%
“…37,47 Baseline scores for each subscale were similar to that obtained in Bailer's study. Among Japanese adult workers, the mean score on the Trait Anxiety Inventory (TAI) was 43, 36 whereas baseline TAI scores in this study were approximately 49 (data not shown). Higher TAI scores for IEI patients compared to normal subjects are consistent with a report by Tonori et al, 35 who described the sustained high anxiety levels among IEI patients.…”
Section: Discussionmentioning
confidence: 53%
“…After providing written informed consent, the subjects were randomly assigned to group A or B using a random number sequence and were subsequently stratified by gender and age (20- 35 . SAI scores below 40 for men and 42 for women are considered to be normal 36 . The sample size required for a mean difference of 7.64 (15%) with an α=0.05 and ÎČ=0.02 was n=36 in each group.…”
Section: Methodsmentioning
confidence: 99%